Evaluation of the cadmium content in some soils of Lattakia Governorate fertilized with phosphate fertilizers. (Submission and Review of Research -Biological Sciences Series, 2025)
This study was conducted with the aim of evaluating the degree of cadmium contamination in the four study sites (Al-Muzaira’a site - Two sites in the village of Al-Quwaiqa, the first was fertilized and the second was not fertilized - Ain Al-Bayda site.) Some physical and chemical properties of the soil were studied and the relationship between the total and available concentration of cadmium and some soil properties was determined. Soil samples were collected from the surface layer (0-20 cm) and the subsurface layer (20-40 cm). the study indicates that soils had different textures. Soil pH was neutral to alkaline. The soils were not saline and the electrical conductivity values ​​were within normal limits, and the studied soils had a medium content of organic matter. The average amount of total cadmium in the four sites ranged between (0.30-0.56 mg/kg) in the surface layer and (0.29-0.48 mg/kg) in the subsurface layer. The average concentration of the available form of cadmium ranged between (0.01-0.015 mg/kg) in the surface layer, and from( 0.007-0.013) mg/kg in the subsurface layer. SPSS was used to access the parameters of the regression model. The concentration of the total form of cadmium was correlated with the pH of the soil solution by a medium-strength correlation (r=0.68). The results of the statistical analysis did not show any correlations between the other studied variables and the two studied forms of cadmium.